2019
DOI: 10.1002/jcb.29132
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lncRNA WWTR1‐AS1 associates with tumor aggressiveness and unfavorable survival in head‐neck squamous cell carcinoma

Abstract: Long noncoding RNAs (lncRNAs) have been recognized as novel biomarkers and therapeutic targets in human cancer including head‐neck squamous cell carcinoma (HNSCC). Here, we aimed to investigate the expression of a novel lncRNA WW domain containing transcription regulator 1 antisense RNA 1 (WWTR1‐AS1) as well as its clinical significance and biological roles in HNSCC. The expression level of endogenous WWTR1‐AS1 in primary HNSCC and paired adjacent nontumor mucosa was evaluated by quantitative reverse‐transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For example, miR-550-1 targets TAZ in acute myeloid leukemia [ 112 ] and miR-455-3p targets TAZ in pancreatic cancer [ 182 ]. Notably, unlike YAP, TAZ has a natural antisense transcript known as WWTR1-AS1; knockdown of this transcript in head–neck squamous cell carcinoma reduces TAZ expression and increases apoptosis [ 183 ]. Though YAP and TAZ are rarely compared in parallel in any given cancer study, it has been shown that TAZ, but not YAP, is upregulated in alveolar rhabdomyosarcoma, and its depletion induces apoptosis and reduces xenograft growth [ 184 ].…”
Section: Yap/taz and Apoptosis In Cancermentioning
confidence: 99%
“…For example, miR-550-1 targets TAZ in acute myeloid leukemia [ 112 ] and miR-455-3p targets TAZ in pancreatic cancer [ 182 ]. Notably, unlike YAP, TAZ has a natural antisense transcript known as WWTR1-AS1; knockdown of this transcript in head–neck squamous cell carcinoma reduces TAZ expression and increases apoptosis [ 183 ]. Though YAP and TAZ are rarely compared in parallel in any given cancer study, it has been shown that TAZ, but not YAP, is upregulated in alveolar rhabdomyosarcoma, and its depletion induces apoptosis and reduces xenograft growth [ 184 ].…”
Section: Yap/taz and Apoptosis In Cancermentioning
confidence: 99%
“…In recent years, more and more studies have focused on lncRNAs as tumor diagnostic markers and potential therapeutic targets. Numerous researches have shown that lncRNAs play an important regulatory role in the development of various cancers, including glioma [ 3–5 ]. For example, linc00319 expresses at a high level in glioma and is significantly associated with poor prognosis of glioma patients, while knockdown of linc00319 impairs cell proliferation, arrests cell cycle and induces cell apoptosis of glioma cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 Hardly any reports are available so far on the aberrant lncRNAs implicated in the cellular dysfunction and signaling pathway of OPMD, despite aberrant lncRNAs having been implicated in the biological behavior of OSCC. [16][17][18][19][20][21] For instance, lncRNA AC007271.3 promotes cell proliferation, invasion, migration, and inhibits cell apoptosis of OSCC via the Wnt/β-catenin signaling pathway. 16 LncRNA LINC00961 inhibited cell proliferation and invasion of OSCC through the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%